2020
DOI: 10.1097/cad.0000000000000901
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the mechanisms of action of parecoxib in the MG-63 osteosarcoma cell line

Abstract: Different types of tumors often present an overexpression of cyclooxygenase-2. The aim of this study was to evaluate the effects of parecoxib (NSAID, cyclooxygenase-2 selective inhibitor) in the behavior of the human osteosarcoma MG-63 cell line, concerning several biological features. Cells were exposed to several concentrations of parecoxib for 48 hours. Cell viability/proliferation, cyclooxygenase-2 expression, morphologic alterations, membrane integrity, cell cycle evaluation, cell death and genotoxicity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It has been reported that parecoxib could improve the postoperative analgesic effect and immune function when used for multimodal analgesia, and further postpone postoperative cancer recurrence [ 12 , 13 ]. Other studies have reported that parecoxib shows antitumor effects against human osteosarcoma, glioblastoma, and intestinal cancers [ 14 16 ]. Studies have further revealed the important role of parecoxib in the inhibition of vascular formation in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that parecoxib could improve the postoperative analgesic effect and immune function when used for multimodal analgesia, and further postpone postoperative cancer recurrence [ 12 , 13 ]. Other studies have reported that parecoxib shows antitumor effects against human osteosarcoma, glioblastoma, and intestinal cancers [ 14 16 ]. Studies have further revealed the important role of parecoxib in the inhibition of vascular formation in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A case report describes an osteosarcoma patient receiving the cyclooxygenase 2 (COX2) inhibitors celelecoxib and thalidomide one month after treatment with lung metastases. It has also been found that celecoxib and thalidomide inhibit proliferation of osteosarcoma cells in a dose-dependent manner 29 . These studies support anti-inflammatory agents as potential therapeutic strategies for osteosarcoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…CD3 represents all T lymphocytes, which can also be divided into CD4+ T cells and CD8+ T cells. Among them, CD4+T cells mediate the functions of helper T cells (T), NKT cells, macrophages, and dendritic cells, while CD8+ lymphocytes mediate the functional changes of cytotoxic T lymphocytes (CTL) [12,13]. Te PBLS detection can evaluate the changes of lymphocyte subsets and the steady-state changes of lymphocyte subsets.…”
Section: Discussionmentioning
confidence: 99%